2022
DOI: 10.3390/ijerph19148635
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits of Patients with Coronary Artery Disease: A Case-Control Study from Pakistan

Abstract: Background: Adults in South Asian countries have high chances of developing coronary artery disease (CAD) as compared to the developed nations. CAD is among the primary non-communicable causes of death in this region. Dyslipidemia, obesity, smoking hypertension, diabetes are considered as important risk factors for CVD. Methods: A case-control study was conducted, with data was collected from the Punjab Institute of Cardiology in Lahore and the University of Lahore Teaching Hospital. A total of 500 subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Regular utilization of fast food might contribute to obesity along with increasing the risk of various systematic diseases affecting various organs [18]. In the current study, the mean age and BMI of the participants who were taking a fast-food were 38.89± 6.89 and 26.14 ±2.87 respectively, while the mean and BMI of those were not consuming them 38.42±7.31 and 25.57± 3.24 accordingly that indicates a clear variation of BMI in both, however, a study conducted by Hanif MK et al reported the same results of difference of BMI among both [19]. The rate of obesity in fast-food users was more common 178 (43.20 %) were obese, while 234 (56.79%) had a normal weight, however, moreover, 5(31.25%) were obese those who were non-consumers of fast food.…”
Section: Discussioncontrasting
confidence: 44%
“…Regular utilization of fast food might contribute to obesity along with increasing the risk of various systematic diseases affecting various organs [18]. In the current study, the mean age and BMI of the participants who were taking a fast-food were 38.89± 6.89 and 26.14 ±2.87 respectively, while the mean and BMI of those were not consuming them 38.42±7.31 and 25.57± 3.24 accordingly that indicates a clear variation of BMI in both, however, a study conducted by Hanif MK et al reported the same results of difference of BMI among both [19]. The rate of obesity in fast-food users was more common 178 (43.20 %) were obese, while 234 (56.79%) had a normal weight, however, moreover, 5(31.25%) were obese those who were non-consumers of fast food.…”
Section: Discussioncontrasting
confidence: 44%
“…A previous study also reported that the Pakistani traditional diet was associated with high cardiovascular risk factors ( 29 ). The majority of Pakistani people eat deep-frying foods and foods high in saturated fats which ultimately increased the risk of CVD ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Pakistani population showed a higher risk ratio of premature CVD mortality attributable to dietary risk. Several factors such as malnutrition ( 28 ) poverty and low diet quality ( 29 ) poor dietary habits ( 30 ) and a poor healthcare system ( 57 ) may contribute to the increased risk of diet-related premature CVD mortality in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…This study is designed to investigate the gene expression and the role of APOA1 and B gene polymorphism with CAD and their relationship with oxLDL, oxHDL and lipid profile in the Pakistani Punjabi population. Punjabis are well known for eating a high fat diet and are genetically predisposed to developing CAD (Hanif et al 2022). Although previous literature shown presence of APO gene polymorphism among CAD (Hassan et al 2015;Liu et al 2014;Niu et al 2017), however, in some studies there were no such association (Bogari et al 2015;Casillas-Muñoz et al 2018;Srivastava et al 2013).…”
Section: Introductionmentioning
confidence: 94%